ANALISIS KEPUASAN PENUMPANG TERHADAP KUALITAS PELAYANAN PROTOKOL KESEHATAN DALAM PENERBANGAN RUTE DOMESTIK - Ramadhanty, Amanda Hanna; Suardana, I Wayan; Sofia Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
The quality of service provided by a company is an essential aspect, thus, service quality should be a focal point for every companies management. In this study, the quality of service regarding health protocols provided by airports and airlines to passengers on domestic routes flights is discussed. High quality service is required to increase passenger satisfaction. The purpose of this study is to discover the level of satisfaction of tourists who receive health protocol services on domestic flights. The data collection techniques in this study are observation, questionnaires and literature study. The sampling technique used is accidental sampling. The number of samples used was 90 respondents. The data analysis technique used is quantitative descriptive analysis. Based on the results of the discussion, it has been verified that the health services implemented by airports and airlines on domestic routes have an impact on passenger satisfaction. This means that passengers are satisfied with the health protocol services provided by the airport and airline.